Pengembangan Media Pembelajaran Animasi Powtoon pada Materi Segiempat Kelas VII SMP - Clara Julia Tekkay; Usman Mulbar; Sahid (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2022)
This research aims to develop and produce learning media using powtoon animation applications that are valid, practical and effective. This research model refers to a ADDIE development model that includes 5 stages namely analysis, design, development, implementation, and evaluation. Research instrument in the form of validation sheets by experts to measure validity aspect; teacher activity observation sheet in managing class to measure practicality aspect; student activity observation sheet, responses, and tests to measure effectiveness aspect. Respondents for the learning media trial are students of class VIII SMP which consists of 27 students. The results showed that the learning media satisfies validity criteria based on the assessment by experts. The learning media satisfies practicality criteria based on the result of teacher activity observation are categorized as good. The learning media satisfies effective criteria based on the result of students activity observation are categorized as very good, students response are categorized as very good, and the percentage of classical completeness from student learning outcomes test reached 85%.